A Factors Affecting the Use of Mobile Learning in Higher Education: An Iranian Context - Haji Zeinolabedini, Mohsen; kasani, hamed abbasi; Salemian, Fardin; raisi, Amin; Mirahmadi, Khaled (Qualitative and Quantitative Methods in Libraries; Vol 9 No 1 (2020): March 2020 Issue, 2020)
The aim of the present study was to investigate the factors influencing the use of mobile learning in the higher education milieu. The research has used the descriptive survey methodology. The participants in this study were 265 professors at Shahid Beheshti University, Tehran, Iran. These participants were chosen randomly. The data were collected by a questionnaire consisting of 42 questions. The questionnaire was developed through a review of existing literature in this field. The reliability of the questionnaire was measured 0/89, using the Cronbach's alpha with SPSS software. To analyze the data and identify the factors, the exploratory factor analysis was run. The results revealed the factors affecting the use of mobile learning in higher education from the perspective of teachers, including technical and technological factors, Attitude factors, personal factors, skills and knowledge factors. Keywords: Higher education, mobile learning, contributing factors, Shahid Beheshti University, Iran.